2021
DOI: 10.22342/jme.12.3.14143.563-580
|View full text |Cite
|
Sign up to set email alerts
|

A Praxeological Analysis of Pre-Service Elementary Teacher-Designed Mathematics Comics

Abstract: Mathematical and didactic knowledge presented in mathematics textbooks and other resources, like mathematics comics (MCs), needs to be evaluated from a lens of appropriate theoretical framework in mathematics education before it can be used as a medium for teaching and learning mathematics.Therefore, this study investigates mathematical and didactic competencies that were reflected in MCs designed by pre-service elementary teachers. The framework for analysing mathematical knowledge embedded in these MCs is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
5
1
1
Order By: Relevance
“…The results of this study differ from several studies which have consistently shown that boys are more independent in mathematics (Frenzel et al, 2010;Putra et al, 2021) and tend to perform better than girls (Dickerson et al, 2015;Ependi & Sopiah, 2015;Mazana et al, 2020). This fact is interesting to discuss because it is related to gender equality today.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The results of this study differ from several studies which have consistently shown that boys are more independent in mathematics (Frenzel et al, 2010;Putra et al, 2021) and tend to perform better than girls (Dickerson et al, 2015;Ependi & Sopiah, 2015;Mazana et al, 2020). This fact is interesting to discuss because it is related to gender equality today.…”
Section: Discussioncontrasting
confidence: 98%
“…Even female students showed more courage in solving math problems in class. The results of this observation are different when compared to research results (Dickerson et al, 2015;Ependi & Sopiah, 2015;Frenzel et al, 2010;Mazana et al, 2020;Putra et al, 2021). Therefore, the researcher wants to know how the relationship between learning outcomes, self-efficacy and gender based on the cut score of students in Majalengka district is based on the cut score that has been set.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Chevallard in Cavalcante & Huang (2022) states that basically no human action exists without clarity or justification, partly or wholly made to be understood and accounted for, including specialization Arabic Arabiyât textbooks. Practical matters such as the use of these textbooks are relevant or not in everyday life, especially in education, requires a logos or knowledge to support this praxis (Putra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The six cultures of the Sumatera Island are incorporated into math comics called 'adventures on the island of Sumatera and learning instruments. The use of comics in the classroom is crucial to meet the demands of teaching mathematics in the 21st century, particularly in enhancing students' creativity and critical thinking abilities (Putra et al, 2021;Toh et al, 2017;van den Heuvel-Pahuizen et al, 2016;van den Heuvel-Panhuizen & Elia, 2011;van den Heuvel-Panhuizen & van den Boogaard, 2008).…”
mentioning
confidence: 99%